Paradigmatic obstacles to improving the health of populations: implications for health policy - McKinlay John B. (Salud Pública de México, 1998)
While there are promising developments in public health, most interventions (both at the individual and community levels) remain focused on "downstream" tertiary treatments or one-on-one interventions. These efforts have their origins in the biomedical paradigm and risk factor epidemiology and the behavioral science research methods that serve as their handmaidens. This paper argues for a more appropriate balance of "downstream" efforts with a more appropriate whole population public health approach to health policy -what may be termed a social policy approach to healthy lifestyles rather than the current lifestyle approach to health policy. New, more appropriate research methods must be developed and applied to match these emerging levels of whole population intervention. We must avoid any disjunction between new upstream policy level interventions and the methods used to measure their effect -appropriate unto the intervention level must be the evaluation method thereof.